Ultrastructural and Chemical Composition of Dentin and Enamel in Lab Animals - Ali Dehghani Nazhvani; Habib Dehghanpour Frashah; Pardis Haddadi; Fatemeh Dehghani Nazhvani (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: Human tooth is clinically the most appropriate material that can be used for in-vitro dental research. However, there are limitations and drawbacks for using human teeth. Therefore, alternatives to samples of human teeth for dental studies are necessary. Purpose: This study purposed to evaluate and compare the microstructure and chemical composition of enamel and dentin of teeth in some lab animals. Materials and Method: In this experimental study, teeth of mouse, rabbit, guinea pig, dog, cat, and sheep were used. Scanning electron microscope observations and X-ray diffraction analysis were performed on samples. Results: This study revealed resemblance in general structure of dentin and enamel between mentioned animals and human. The minimum mean of dentinal tubules diameter is found in guinea pig (0.5µ), while the highest is in cat (1.5µ). Also the lowest and the highest mean intertubular distance was measured respectively in guinea pig (3µ) and sheep (4.8µ) and the maximum and minimum mean diameter of rods was measured in rabbit (6.6µ) and guinea pig (1.5µ), respectively. Conclusion: The recorded details and the measured values indicate great resemblance between dog and human dentin and enamel. Cat is in the second place for dentinal studies; sheep and guinea pig have the least resemblance to human within the scope of the reviewed criteria.